Combination of Osimertinib and Anlotinib May Overcome the Resistance Mediated by in cis EGFR T790M-C797S in NSCLC: A Case Report - Zhou, Rengui (Onco Targets Ther, 2021)
The emergence of epidermal growth factor receptor (EGFR) exon 20 p.C797S is one of the major resistance mechanisms for osimertinib. However, there are no standard of care for non-small cell lung cancer (NSCLC) patients after acquiring EGFR C797S currently, which brings significant challenges to post-osimertinib clinical management. In the present study, we described a 52-year-old female patient with EGFR-mutated stage IV lung adenocarcinoma, who achieved a partial response (PR) to the treatment of gefitinib and osimertinib after acquiring EGFR exon 20 p.T790M-trans-C797S at osimertinib failure. After progression on the combinatorial treatment, allelic configuration shifted to T790M-cis-C797S. The patient subsequently received a regimen of osimertinib and anlotinib combined with chemotherapy, followed by osimertinib and anlotinib maintenance treatment, and achieved a PR lasting for 9 months. At disease progression, concomitant T790M-C797S mutations both in trans and cis were identified. A combination of chemo- and anti-angiogenic therapies was administrated for two cycles and then discontinued because of the poor physical condition of the patient. She passed away soon with an overall survival of 39 months and a post-osimertinib progression survival of 20 months. Our study provides the first clinical evidence that the osimertinib and anlotinib-based regimen may be an effective therapy in overcoming resistance mediated by T790M-cis-C797S. Our case also highlights the importance of dynamically monitoring the mutation status after osimertinib failure, which may provide patients with increased opportunities for targeted therapy and improve post-osimertinib progression survivals.